2022
DOI: 10.1001/jamanetworkopen.2022.1242
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Considerations for the Increased Risk of Mental Health Problems Following Concussion in Youth

Abstract: Elsewhere in JAMA Network Open, Ledoux and colleagues 1 have shared their work on a 10-year provincewide (Ontario, Canada) population-based cohort study on a retrospective health administration data set showing that children aged 5 to 18 years with concussion were at risk for a novel mental health problem. A total of 152 321 youths with concussion and 296 482 youths with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Previous studies have suggested that the association between symptom duration and TBI severity may be stronger than it is with the time since the TBI or the age of the child [88]. This issue should be explored further in future studies by additionally controlling potential confounders [89] (e.g., other health conditions, comorbidities, or also considering developmental stages leading to depressive symptoms) that may affect adolescents between the time of injury and the assessment of post-concussion, depression symptoms, and HRQoL beyond the acute phase of injury.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have suggested that the association between symptom duration and TBI severity may be stronger than it is with the time since the TBI or the age of the child [88]. This issue should be explored further in future studies by additionally controlling potential confounders [89] (e.g., other health conditions, comorbidities, or also considering developmental stages leading to depressive symptoms) that may affect adolescents between the time of injury and the assessment of post-concussion, depression symptoms, and HRQoL beyond the acute phase of injury.…”
Section: Discussionmentioning
confidence: 94%
“…Existing studies have suggested that the persistence of symptoms may be more closely related to TBI severity than to time since TBI or the age of the child [88]. This issue should be further explored in future studies by additionally controlling for potential confounders [89] (e.g., other health conditions, comorbidities, or also considering developmental stages leading to depressive symptoms) that may affect adolescents between the time of injury and the assessment of post-concussion, depression symptoms, and HRQoL in the post-acute injury phase.…”
Section: Discussionmentioning
confidence: 96%
“…Satisfactory reliability was reported for both the total score (Cronbach's α = . 89) and for the scales (Cronbach's α = 0.70-0.80) in groups of children and adolescents with and without multiple symptom burden [12]. Its test-retest reliability was acceptable (intraclass correlation coefficients: 0.42-0.64).…”
Section: Introductionmentioning
confidence: 94%